Photocatalytic Hydrogen Production from Water on Ga, Sn-doped ZnS under Visible Light Irradiation - Leny, Yuliati; Kimi, Melody; Mustaffa, Shamsuddin (Trans Tech Publications, 2014)
Zinc sulfide (ZnS) has been reported to act as a photocatalyts to reduce water to hydrogen. However, ZnS could not work under visible light irradiation due to its large band gap energy. In order to improve the performance of ZnS, Ga and Sn were doped to ZnS. The series of Ga(0.1),Sn(x)-ZnS with various amounts of Sn (x) was prepared by hydrothermal method. XRD patterns suggested that the addition of Ga might reduce the crystallinity of ZnS, suggesting that Ga might inhibit the crystal growth or agglomeration of ZnS. On the other hand addition of Sn did not much affect the structure of the Ga(0.1)-ZnS. The DR UU-visible spectra confirmed the red shift of the absorption edge with the addition of Ga due to the reduced band gap energy, while the addition of Sn did not much shift the absorption edge of the Ga(0.1)-ZnS to longer wavelength. FESEM images showed that all the prepared samples have sphere-shaped particles and no remarkable change was observed with the addition of Ga or Sn. The photocatalytic hydrogen production from water was carried out at room temperature in the presence of sacrificial agent under visible light irradiation. While ZnS did not show activity under visible light, all the prepared Ga(0.1)-ZnS and Ga(0.1),Sn(x)-ZnS samples exhibited photocatalytic activity for hydrogen production. The highest hydrogen production was achieved on Ga(0.1),Sn(0.01)-ZnS, which activity was ca. three times higher than that of the single doped Ga(0.1)-ZnS. This study clearly showed that Sn acted as a good co-dopant to increase the photocatalytic activity of Ga(0.1)-ZnS for hydrogen production from water under visible light irradiation.